Corrosion of rock reinforcement in underground excavations - Hassell, Rhett Colin (Curtin University, 2008)
The effect of corrosion on the performance of rock support and reinforcement in Australian underground mines has not been widely researched and is generally not well understood. This is despite the number of safety concerns and operational difficulties created by corrosion in reducing the capacity and life expectancy of ground support. This thesis aims to investigate corrosion and relate how the environmental conditions in Australian underground hard rock mines impact on the service life of rock support and primarily rock reinforcement. Environmental characterisation of underground environments was completed at a number of mine sites located across Australia. This provided an improved understanding of the environmental conditions in Australian underground hard rock mines. Long-term testing on the impact of corrosion on the load bearing capacity of reinforcement and support under controlled experimental conditions was conducted in simulated underground environments. Rock reinforcement elements were examined in-situ by means of overcoring of the installed reinforcement and surrounding rock mass. Laboratory testing of the core determined changes in load transfer properties due to corrosion damage. These investigations provided an excellent understanding of the corrosion processes and mechanisms at work. Corrosion rates for a range of underground environments were established through the direct exposure and evaluation of metallic coupons in underground in-situ and simulated environments.It was found that the study of corrosion is challenging due to the time required to gather meaningful data. In particular, the wide range of materials that comprise ground support systems means that it is impossible to examine all the possible combinations of variables and their potential influence on the observed levels of corrosion and measured corrosion rates. Despite these challenges, the systematic investigation has resulted in new corrosivity classifications for both groundwater and atmospheric driven corrosion processes for various reinforcement and support systems used in the Australian underground mining industry. Previous corrosivity classifications were not found applicable. Furthermore, these new corrosivity classifications are simpler than previous classifications and corrosion rates may be predicted from readily obtained measurements of ground water dissolved oxygen and atmospheric relative humidity. Different types of reinforcement and surface support systems have been rated with respect to their corrosion resistance and estimates have been made for the expected service life for various rates of corrosion.